The Jordanian Stock Market-Should You Invest in It for Risk Diversification or Performance? - Petri, Martin; Saadi-Sedik, Tahsin (Washington, D.C. : International Monetary Fund, 2006)
We analyze the performance of the Amman Stock Exchange (ASE) and its integration with other markets. Using cointegration techniques, we find that the ASE and other Arab stock markets are cointegrated, which implies little long-run risk diversification. However, there is no cointegrating relationship between the ASE and other emerging or developed stock markets. Two of the main regional stock markets-Kuwait and Saudi Arabia-Grangercause the Jordanian stock market. The paper finds that there may have been some overvaluation at end-2005, but that the market correction in early 2006 and strong recent earnings growth have reduced overvaluation concerns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet